HEALTHCARE UTILISATION, PROVIDER CHOICE AND OUT-OF-POCKET EXPENDITURE IN NIGERIA: EVIDENCE FROM THE 2023–2024 GENERAL HOUSEHOLD SURVEY PANEL. - S.B. Kaze; J.E., Ajaba; D.P. Anthony; M. Anche; P.O. Onyia; M.A. Gang (African Journal of Health, Safety and Environment, 2026)
Out-of-pocket (OOP) payment remains a major source of healthcare financing in Nigeria, yet recent nationally representative evidence linking healthcare utilisation, provider choice and household spending is limited. This study assessed healthcare utilisation, provider pathways, OOP expenditure and factors associated with household spending using the Nigeria General Household Survey Panel, Wave 5, 2023–2024. A cross-sectional analysis included 6,357 individuals reporting illness or injury in the preceding four weeks, nested within 3,313 households and 508 survey clusters. Cross-sectional weights and survey-adjusted descriptive estimates were applied. Household OOP expenditure was analysed using a two-part model: logistic regression for any OOP payment and a Gamma model with log link among positive spenders. Among all 6,357 individuals, mutually exclusive provider pathways were formal clinical providers (50.6%), chemists or patent medicine vendors (36.6%), traditional or spiritual providers (2.5%), other providers (0.1%) and no care (10.1%); these total 99.9% because of rounding, indicating that 89.9% sought care. Among the 5,726 individuals who sought care, 97.8% incurred OOP expenditure. Median four-week expenditure was NGN 3,200 per care user and NGN 5,800 per affected household. Prescription medicines accounted for 67.8% of mean outpatient expenditure. Each additional recently ill household member was associated with higher odds of any household OOP payment (aOR 2.07, 95% CI: 1.57–2.73) and higher positive expenditure (ER 1.32, 95% CI: 1.26–1.39). The richest households also had higher positive expenditure than the poorest (adjusted odds ratio: 1.33; 95% CI x-y). OOP payment remained nearly universal among care users, with medicines dominating outpatient costs.